ANALISIS VOLUME PERDAGANGAN DAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH PELANTIKAN PRESIDEN DAN WAKIL PRESIDEN - Nurheriyani, Adila (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
Purpose of this research to analyze the differences in trading volume activity and abnormal returns before and after the inauguration of the president and vice president in 2014. This study is an empirical study. The type of data used quantitative and qualitative data. Source of data used secondary data. The study population food and beverage companies who listed in Indonesia Stock Exchange as many as 13 companies. The sampling technique used census. Data collection techniques used documentation and literature studies. Data were analyzed used paired sample t-test. Results of the analysis showed that there were differences in the average trading volume activity of food and beverage companies listed in Indonesia Stock Exchange before and after the inauguration of the president and vice president in 2014 with a p value 0,003 < 0,05. There is no difference in average abnormal stock returns of food and beverage companies listed in Indonesia Stock Exchange before and after the presidential inauguration Jokowi and vice president Jusuf Kalla 2014 with p value 0,078 > 0,05. Keywords: trading volume activity, abnormal return and event study